Experiências auto formativas de uma graduanda ao trabalhar como acompanhante pedagógica inclusiva de uma criança autista - COSTA, Amanda Lohanna da Mota (2024)
Acting as an inclusive pedagogical companion, for the initial training of teachers, is a practice that provides an opportunity to understand the autistic spectrum and experience experiences that contribute to the training of future teachers. In this sense, the need to understand the experiences and challenges faced when teaching students with ASD is evident. In view of this situation, I analyze, in this research, self-training experiences lived, when carrying out the pedagogical follow-up of a child with ASD, aiming to understand teaching learning that such experiences contribute to my training as a future teacher in the early years. For this, I assume the qualitative research in the narrative approach, from the reports of my performance in this context, registered in my personal diaries and analyzed through Textual Discursive Analysis (DTA). Thus, I was able to attribute new meanings to the experiences lived with the autistic child, from an epistemological point of view, obtaining as a result that the process of constant observation and reflection made it possible to reinvent myself as a professional in constant formation and this experience as an inclusive pedagogical companion empowered me for the classroom, for a future teacher who is more attentive in noticing my students' difficulties, having developed sensitive listening.